FINANCIAL ANALYSIS OF CATTLE BREEDING FARM IN SLEMAN DISTRICT - Shanti Emawati; Endang Tri Rahayu (UPT Penerbitan Universitas Jember, 2012)
The research was conducted to determine the feasibility of financial on beef cattle farming and calculate the Break Even Point (BEP) in Sleman District. Survey methods was done to collect primary data at the farm level and secondary data from related institution. Criteria used to analyze the feasibility of financial were consisted of Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PPC), based on 7 years investment and 12% annual discount factor. The result showed that based on NPV, IRR, BCR and PPC analysis, the most feasible investment of cattle breeding farm under farmers’ condition was achieved when farmers keep Limousine grade cattle, followed by Simmental and Ongole grade cattle. In term of PPC, farmers who keep Limousine grade cattle were able to return the investment during 3.25 years while for Simmental and Ongole grade cattle were 3.44 and 5.19 years, respectively. The BEP of keeping Simmental, Limousine and Ongole grade cattle were 8, 9 and 7 cows/farmer, respectively, which mean that farmers will annually benefited from keeping cattle when the number of cows was larger than those of BEP.